RESPONS EMBRIOGENESIS MIKROSPORA TANAMAN TEBU (Saccharum spp.) PADA SUHU DAN LAMA INKUBASI CABANG MALAI DI DALAM MEDIUM B - Suaib Suaib; W. Mangoendidjojo; Mirzawan PDN; A. Indrianto (The East Java Biological Society, 2008)
Microspore embryogenesis under different temperature and time duration pretreatments of spike segments of Saccharum spp., clone PS862 has been studied in in-vitro laboratory of Faculty of Biology Gadjah Mada University, Yogyakarta. Combination pretreatments of a 4 and 34° C of temperatures, and 0, 2, 4, and 7 days duration of incubation of spike segments in the B medium were studied in this observation. A B5 medium of Gamborg supplemented with 2 mgl-1 2.4-D or 2 mg.l-1 NAA was also studied on the formation of proembryos and embryos under 25°C temperature in the dark for at least 30 days. Results of the research showed that the percentage of viable microspores was decreased as simultaneously prolonged of the time of duration in the B medium either under low temperature or under high temperature pretreatments tested. Incubation of spike segments under low temperature after 4 days was decreased the percentage of viable microspores over 44%. In contrast, under high temperature pretreatment the percentage of viable microspores was decreased over 54%. The higher percentage (12.5%) of binucleate microspores was achieved after 7 days incubation of spike segments in the B medium under the low temperature compared to the high temperature (7.14%). Besides, the higher percentage (87.5%) of simmetrical binucleate microspores as proembryo and embryo precursor was obtained after 2 days incubation in the B medium under the low temperature compared to the high temperature (79.0%). Finally, only B5 medium supplemented with 2 mgl-1 of NAA was yielded the proembryos and embryos after 30 days of incubation.